Metallurgy, Ballistics and Epistemic Instruments: The Nova scientia of Nicolò Tartaglia - A New Edition - Matteo Valleriani (Sources 6: Max Planck Research Library for the History and Development of Knowledge, 2013)
In 1537, Nicolò Tartaglia (1500-1557), a mathematician from Brescia, published "Nova scientia." It was this work that led to the foundation of the modern science of ballistics. Tartaglia's intention was to create a purely mathematical science based on axioms, which was fundamental to the entire subject of mechanics, starting with a limited number of principles and arriving at a series of propositions through a rigid procedure of deduction. Nevertheless, as Tartaglia himself states, his motive was fundamentally practical and connected to the activities of the sixteenth-century bombardier. A new edition of Nicolò Tartaglia's "Nova scientia," based on the 1558 print run of the second enlarged edition (1550), shows how the emergence of theoretical ballistics was a consequence of the technological innovations that took place in the frame of the practice of iron casting at the turn from the fifteenth to the sixteenth century.